2016
DOI: 10.1007/s00221-016-4593-9
|View full text |Cite|
|
Sign up to set email alerts
|

Coordination of muscles to control the footpath during over-ground walking in neurologically intact individuals and stroke survivors

Abstract: The central nervous system (CNS) is believed to use the abundant degrees of freedom of muscles and joints to stabilize a particular task variable important for task success, such as footpath during walking. Stroke survivors often demonstrate impaired balance and high incidences of falls due to increased footpath variability during walking. In the current study, we use the uncontrolled manifold (UCM) approach to investigate the role of motor abundance in stabilizing footpath during swing phase in healthy indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…No mention of strategies for avoiding fatigue was made in two studies [38,41]. The performance variables and elemental variables were clearly identified in all studies, but two studies did not justify the choice of elemental variables [24,40].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 4 more Smart Citations
“…No mention of strategies for avoiding fatigue was made in two studies [38,41]. The performance variables and elemental variables were clearly identified in all studies, but two studies did not justify the choice of elemental variables [24,40].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…One study was found for each of the following pathologies: multiple sclerosis [44], olivo-ponto-cerebellar atrophy [45] and spinocerebellar degeneration [46]. With regard motor tasks, seven studies investigated multi-finger pressing tasks [24,32,39,41,[43][44][45], four reaching [34][35][36][37], three posture stabilization in quiet standing [25,33,43], one load release while standing [46], one pressing and prehension [42], one wrist and fingers extension [40], and one walking [38]. The most commonly used performance variables were the trajectory of center of pressure in balance tasks [25,33,43,46], total pressing force in finger pressing tasks [32,39,41,44,45] and hand position in reaching tasks [34,35,37].…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations